Provided that p is a real value not equal to 6, the value of x is (c) [tex]\mathbf{x = \frac{p+1}{p - 6}}[/tex]
The equation is given as:
[tex]\mathbf{p^2-5p-6-x(p-6)^2=0}[/tex]
Expand
[tex]\mathbf{p^2-6p + p-6-x(p-6)^2=0}[/tex]
Factorize
[tex]\mathbf{p(p-6) + 1(p-6)-x(p-6)^2=0}[/tex]
Factor out p -6
[tex]\mathbf{(p+1)(p-6)-x(p-6)^2=0}[/tex]
Divide through by p - 6
[tex]\mathbf{(p+1)-x(p-6)=0}[/tex]
Rewrite as:
[tex]\mathbf{x(p-6) = (p+1)}[/tex]
Make x the subject
[tex]\mathbf{x = \frac{p+1}{p - 6}}[/tex]
Hence, the value of x is (c) [tex]\mathbf{x = \frac{p+1}{p - 6}}[/tex]
Read more about equations and real constants at:
https://brainly.com/question/17118747